2017
DOI: 10.1016/j.buildenv.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Ten questions concerning occupant behavior in buildings: The big picture

Abstract: Occupant behavior has significant impacts on building energy performance and occupant comfort. However, occupant behavior is not well understood and is often oversimplified in the building life cycle, due to its stochastic, diverse, complex, and interdisciplinary nature. The use of simplified methods or tools to quantify the impacts of occupant behavior in building performance simulations significantly contributes to performance gaps between simulated models and actual building energy consumption. Therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
219
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 430 publications
(234 citation statements)
references
References 90 publications
(131 reference statements)
0
219
0
15
Order By: Relevance
“…A recently-published big-picture paper summarised the gaps of this field of research as well (Hong et al 2016). Researchers articulated the main gaps here as: (1) oversimplified or disregarded occupant behaviours throughout the building operation process, (2) lack of common agreement on validity and applicability of occupant behaviour modelling and simulation approaches, and (3) unclear humancentred interdisciplinary solutions.…”
Section: Gaps In Energy-related Occupant Behaviour Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A recently-published big-picture paper summarised the gaps of this field of research as well (Hong et al 2016). Researchers articulated the main gaps here as: (1) oversimplified or disregarded occupant behaviours throughout the building operation process, (2) lack of common agreement on validity and applicability of occupant behaviour modelling and simulation approaches, and (3) unclear humancentred interdisciplinary solutions.…”
Section: Gaps In Energy-related Occupant Behaviour Literaturementioning
confidence: 99%
“…With invasive selfreported questionnaire surveys, for example, subjects are recruited participants in that they are aware of the scope of research and that they are being observed. Another approach of observation tool categorization was presented recently by Hong et al (Hong et al 2016). Physical sensing techniques are presented to be used for objective measurements, such as smart metering, BMS data, indoor and outdoor environmental data, and occupant interaction with control systems.…”
Section: Tools Used To Investigate Energy-related Occupant Behaviourmentioning
confidence: 99%
“…Researchers now broadly recognize the contextual (rather than purely environmental) factors influencing the human-building interaction [10][11][12][13][14][15][16][17]. Explorations regarding the achievement of energy-efficient usage in the building sector are today established around the understanding of the socio-technical link between building occupants' behavior and the use of building technologies, energy services, and controls [9]. Abrahamse, et al, [12] anticipated this interdisciplinary approach as a two-way exchange of knowledge from socio-technical disciplinary fields of sciences: "sociologists can provide more insight into macro-level factors that shape […] …”
Section: Needs For Interdisciplinary Studiesmentioning
confidence: 99%
“…The availability of more interdisciplinary occupants' data-driven knowledge-and behavioral models-to simulate varying parameters associated with specific building features or climate can further provide insights into actual energy performance fluctuations in buildings. This will help to bridge the accuracy gap between the predicted and actual human-building interaction, and, hence, energy performance, consumption, and comfort [9,54,95,96].…”
Section: 23modeling and Simulation Advancementsmentioning
confidence: 99%
See 1 more Smart Citation